¿Cómo mejorar la eficacia comercial de los restaurantes de comida rápida en la ciudad de Lima? - Miñano Martínez, Sergio André (2022)
The current investigation attempts to demonstrate how to improve the commercial efficiency of a fast food company, this being measured in terms of sales levels. Two variables that potentially contribute to the aforementioned objective are studied: promotions and customer service speed. The research makes use of a survey as a data collection technique, and secondary data from Euromonitor, INEI and CPI, being of a diachronic type, and of mixed source. The approach is quantitative and a total of 391 effective surveys will be applied to fast food consumers. The present work shows that improvement efforts in promotions, and customer service speed have a great potential to contribute to sales when investing in advertising in electronic media - mainly - and when the product is promoted as a combo meal at low prices.